Right congenital diaphragmatic hernia associated with hepatic pulmonary fusion - Maher Al-Zaiem; Atiah Alzahrani; Enas I Raml; Nedaa Alsulaimani; Lujain Alzahrani; Ahmad Turki (Elsevier, 2023)
Hepato-pulmonary fusion (HPF) is a rare congenital malformation that may be associated with right-sided congenital diaphragmatic hernias (CDH). According to our literature review, only 34 cases have been reported. We report herein two cases of hepatopulmonary fusion diagnosed during the operative repair of right-sided CDH in term neonates and discuss different modalities of managing these cases.